2003
DOI: 10.1038/sj.ejhg.5200942
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterisation of the retinitis pigmentosa 1-like1 gene (RP1L1): a novel candidate for retinal degenerations

Abstract: Retinitis pigmentosa (RP) is the most common form of inherited retinopathy, with an approximate incidence of 1 in 3700 individuals worldwide. Mutations in the retinitis pigmentosa 1 (RP1) gene are responsible for about 5 -10% cases of autosomal dominant RP. The RP1 gene is specifically expressed in the photoreceptor layers of the postnatal retina and encodes a predicted protein characterised by the presence of two doublecortin (DC) domains, known to be implicated in microtubule binding. We identified and chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 23 publications
(23 reference statements)
1
30
0
Order By: Relevance
“…RP1L1 is expressed primarily in cones and rods. 17 The first 350 amino acids are conserved and share high similarity with RP1, a protein that can be mutated in autosomal dominant and recessive forms of RP. 1820 This conserved region contains two doublecortin domains.…”
Section: Discussionmentioning
confidence: 99%
“…RP1L1 is expressed primarily in cones and rods. 17 The first 350 amino acids are conserved and share high similarity with RP1, a protein that can be mutated in autosomal dominant and recessive forms of RP. 1820 This conserved region contains two doublecortin domains.…”
Section: Discussionmentioning
confidence: 99%
“…12 The RP1L1 gene was originally cloned as a gene derived from common ancestors as a retinitis pigmentosa 1 (RP1) gene, which is responsible for 5-10% of autosomal dominant retinitis pigmentosa worldwide, on the same Chromosome 8. [13][14][15][16][17] A number of attempts have been made to identify mutations in RP1L1 in various retinitis pigmentosa patients with no success. An immunohistochemical study on cynomolgus monkeys showed that RP1L1 was expressed in rod and cone photoreceptors, and RP1L1 is thought to play important roles in the morphogenesis of the photoreceptors.…”
mentioning
confidence: 99%
“…An immunohistochemical study on cynomolgus monkeys showed that RP1L1 was expressed in rod and cone photoreceptors, and RP1L1 is thought to play important roles in the morphogenesis of the photoreceptors. 13,18 Heterozygous RP1L1 knockout mice were reported to be normal, whereas homozygous knockout mice develop subtle retinal degeneration. 18 However, the RP1L1 protein has a very low degree of overall sequence identity (39%) between humans and mice compared with the average values of sequence similarity observed between humans and mice proteins.…”
mentioning
confidence: 99%
“…Doublecortin domain containing 2 , DCDC2 , has been suggested to play a causative role in reading disabilities and has been implicated as a susceptibility gene for Dyslexia [25,26]. Retinitis Pigmentosa 1 , RP1 , and Retinitis Pigmentosa like 1 , RP1L1 , are associated with inherited blindness [27,28]. The known CNS expression pattern and possible function of the DCX gene superfamily are summarized in Table 1.…”
Section: Introduction Of Shrna In the Developing Brain: Pros And Consmentioning
confidence: 99%